Exposure to domestic abuse and the subsequent risk of developing periodontal disease. Issue 12 (December 2022) - Minhas, Sonica; Qian Hui Lim, Rachel; Raindi, Devan; Gokhale, Krishna M.; Taylor, Julie; Bradbury-Jones, Caroline; Bandyopadhyay, Siddhartha; Nirantharakumar, Krishnarajah; Adderley, Nicola J.; Singh Chandan, Joht
Abstract: Aims: Periodontal disease and domestic abuse (DA) are significant public health problems. Previous cross-sectional evidence indicates an association between DA exposure and development of periodontal disease. There have been no large-scale cohort studies exploring this relationship in a UK-setting. Our aim was to conduct a population-based retrospective open cohort study to explore the association between DA exposure and the subsequent development of general practitioner (GP)-coded periodontal disease. Materials and methods: We undertook a retrospective open-cohort study using the IQVIA Medical Research Database (IMRD) UK database between the 1 st January 1995 to 31 st January 2021. Women (aged 18 years and over) exposed to DA were matched by age, deprivation, and smoking status to up to 4 unexposed women, all of whom had no pre-existing record of periodontal disease. Cox regression analysis was used to calculate crude and adjusted hazard ratios (HRs) to describe the risk of developing periodontal disease in the exposed group. Results: 23429 exposed patients were matched to 69815 unexposed patients. During the study period, 78 exposed patients had developed GP-recorded periodontal disease compared to 154 in the unexposed group, translating to an IR of 94.18 per 100, 000 person years (py) and 54.67 per 100, 000 py respectively. Following adjustment for key covariates, this translated to an aHR of 1.74 (95% CI 1.31–2.32), which was robust during our sensitivity analysis. Conclusions: Our results provide further evidence that DA exposure is associated with increased risk of developing periodontal disease. There is a need for swift implementation of public health policies to improve surveillance, reporting, and prevention of DA. Abstract : Domestic abuse; Periodontal disease; Periodontitis; Gingivitis.